Eksplorasi Motif Batik pada Artisan Enterpreneurship Guna Meningkatkan Nilai Jual - Ni Putu Rizky Arnani; Uswatun Hasanah; Luthfi Awwalia (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
The creative industry plays a crucial role in boosting economic growth and creating job opportunities. One tangible manifestation is artisan entrepreneurship, which focuses specifically on handmade products such as batik. Batik holds not only aesthetic value but also philosophical meaning, reflecting culture and local wisdom. This community service program was carried out to enhance the marketing skills of the batik community in Tanjungbumi, Bangkalan, Madura. The goal is for artisans to gain a deeper understanding of the philosophy behind the batik they produce. As a result, artisans can increase the market value of their batik products. The Participatory Action Research (PAR) method was employed, actively involving artisans in the educational process. The results show that the ability to understand and convey the meaning behind batik motifs can enhance the value and competitiveness of batik in the market. Therefore, it is essential to continuously develop artisans' communication skills and knowledge.